Evolving the core product: Stakeholder’s perceptions of the NCAA wrestling season - Coyte G. Cooper; Erianne A. Weight (Journal of Applied Sports Management, 2011)
During the past 25 years, athletics directors have made the decision to eliminate more than 130 National Collegiate Athletic Association (NCAA) wrestling programs (NCAA Sports Sponsorship, 2008). While many advocates of college wrestling in the United States have blamed Title IX for program eliminations, several scholars have illustrated that the attrition of men’s nonrevenue teams is instead due to the outlandish spending on men’s basketball and men’s football within athletic departments (Marburger & Hogshead-Makar, 2003, Zimbalist, 2003). With the economic challenges and the “arms race” occurring at the Division I level, it is imperative for college wrestling to develop strategies to ensure that each of its programs are self-sustainable in future years. The purpose of the study was to survey stakeholders of intercollegiate wrestling (coaches [N = 77], consumers [N = 954], officials [N =29], and student-athletes [N = 279]) to identify potential strategies to enhance the quality of the college wrestling product. In addition to several critical suggestions discussed in the article, stakeholders unanimously supported an adjustment in the college wrestling post-season to avoid March Madness (M = 4.95; SD = 1.23) and the high school wrestling state championships (M = 4.43; SD = 1.41).
Keywords: NCAA wrestling; product assessment; program eliminations; marketing